Subsets of memory CD4+ T cell and bactericidal antibody response to Neisseria meningitidis serogroup C after immunization of HIV-infected children and adolescents. - Lucimar G Milagres; Priscilla R Costa; Giselle P Silva; Karina I Carvalho; Wânia F Pereira-Manfro; Bianca Ferreira; Daniella M Barreto; Ana Cristina C Frota; Cristina B Hofer; Esper G Kallas (PLoS ONE)
Meningococcal disease is endemic in Brazil, with periodic outbreaks and case fatality rates reach as high as 18 to 20% of cases. Conjugate vaccines against meningococci are immunogenic in healthy children. However, we have previously shown a poor bactericidal antibody response to a Men C conjugate vaccine in Brazilian HIV-infected children and adolescents after a single vaccine administration. The goal of the present work was to investigate associations between bactericidal antibody response induced by MenC vaccine and the frequency and activation profile (expression of CD38, HLA-DR and CCR5 molecules) of total CD4+ memory T cell sub-populations in HIV-1-infected children and adolescents. Responders to vaccination against MenC had a predominance (about 44%) of CD4+ TINTERMEDIATE subset followed by TTRANSITIONAL memory subset (23 to 26%). Importantly, CD4+ TINT frequency was positively associated with bactericidal antibody response induced by vaccination. The positive correlation persisted despite the observation that the frequency TINT CD38+HLA-DR+ was higher in responders. In contrast, CD4+ TCENTRAL MEMORY (TCM) subset negatively correlated with bactericidal antibodies. In conclusion, these data indicate that less differentiated CD+ T cells, like TCM may be constantly differentiating into intermediate and later differentiated CD4+ T cell subsets. These include CD4 TINT subset which showed a positive association with bactericidal antibodies.